Analisis Kinerja Keuangan pada Usaha Mikro Kecil (Studi Kasus Usaha Roti Kacang Mpok Atik di Kota Tebing Tinggi) - Tamba, Greace Havana; Samosir, Hendrik Elisa Sutejo; Siahaan, Audrey Margareth (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to find out about the financial performance development of small micro-enterprises in a case study of peanut butter bread in a high-rise city. This research is a kind of field research. (field research). The method used is qualitative descriptive. The data collection techniques used are observations, interviews and documents. The research uses qualitative data from financial statements such as financial position reports and profit and loss reports because in this study the researchers study, analyze and draw conclusions from the financial reports of the enterprise. Based on the results of the research and analysis of the profitability ratio using the formula GPM, NPM, ROA, and ROE show that the enterprise has increased and decreased each year, the financial performance of such enterprise is assessed well in the course of the last 3 years starting from 2021-2023 If the industry average is 30% to assess the good or badness of a enterprise, then that enterprise only good in the calculation of the gross profit margin (GPM) that is above the average of the industry. In the calculation of other profitability ratios, the business of sagu flour has experienced an increase in earning profits. (in-profit). But, the average calculation results of the enterprise starting in 2021-2023 are better than in 2022.